2018
DOI: 10.1097/bth.0000000000000186
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of a Radial Nerve Branch to the Brachialis Nerve for Restoration of Elbow Flexion

Abstract: Nerve transfers for brachial plexus reconstruction and the treatment of peripheral nerve injury have demonstrated excellent clinical outcomes and may be superior to nerve grafting. Previously described nerve transfers for restoration of elbow flexion include the Oberlin (ulnar to musculocutaneous) and double fasicular (median to biceps and ulnar to brachialis) transfers. However, these transfers cannot be performed in patients with loss of elbow flexion and concomitant high median and ulnar nerve injury. Other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The series by Bertelli and Ghizoni (2014) supports the transfer of the anconeus nerve to the anterior division of the axillary nerve as an effective and reliable method of deltoid reinnervation. Recently, Chepla and Bafus (2018) described the use of the anconeus nerve transferred to the brachialis nerve to restore elbow flexion as an alternative to the Oberlin technique. Transfer to the biceps branch (Figure S1) or to the anteriorly transposed ulnar nerve are further possible options.…”
Section: Resultsmentioning
confidence: 99%
“…The series by Bertelli and Ghizoni (2014) supports the transfer of the anconeus nerve to the anterior division of the axillary nerve as an effective and reliable method of deltoid reinnervation. Recently, Chepla and Bafus (2018) described the use of the anconeus nerve transferred to the brachialis nerve to restore elbow flexion as an alternative to the Oberlin technique. Transfer to the biceps branch (Figure S1) or to the anteriorly transposed ulnar nerve are further possible options.…”
Section: Resultsmentioning
confidence: 99%
“…In general, nerve transfers recover relatively quickly compared to nerve grafts, which is reported to be one of the most important factors in the number of viable motor axons 1,10,12) . This technique allows the transfer of regenerating motor axons very close to the neuromuscular junction of the elbow flexors, minimizing the distance and time required for the regenerating front to reach the target muscle 2,[10][11][12]14) . Therefore, patients with prolonged onset of disease can also be candidates for this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The muscle unit along with its innervation may be transferred to reestablish the flexion of elbow (19). Nerve transfer procedures performed for the brachial plexus reconstruction and peripheral nerve injuries have given better outcomes than the nerve grafting (20). Literature search revealed that there are only a very few studies available about the UCN.…”
Section: Introductionmentioning
confidence: 99%